Modeling elevated-temperature mechanical behavior of high and ultra-high strength steels in structural fire design. (15th December 2017) - Neuenschwander, Martin; Scandella, Claudio; Knobloch, Markus; Fontana, Mario
Highlights: Established constitutive fire design models for mild carbon steels only restrictedly valid for highstrength steels. Model shortcomings in depth quantified with consistent database and improved stiffness and strength reductions proposed. Safety of structural fire designs mainly impeded by overestimation of the high-temperature strength in fire design models. Graphical abstract: Abstract: High and ultra-high strength steels are increasingly used in structures of tall and super-tall buildings, where fire safety has a substantial impact on the structural design. However, more widespread employment in engineering practice is substantially impeded by the lack of suitable design models for the constitutive mechanical behavior of such steels at elevated temperatures; and respective available experimental research is limited to investigations of unusually thin plate material with respect to structural applications. The present study completes the current database with an extensive series of strain-rate controlled tensile tests at different strain-rates with coupon specimens from high and ultra-high strength steel plates of varying thickness, and approves on the basis of this novel most comprehensive and consistent database that existing constitutive fire design models for mild carbon steels are only restrictedly adoptable for high strength steels. Analysis of the impact of the revealed model shortcomings at the material level on structural fire designs shows that the model's overestimation of the elevated-temperature yield strength leads to unsafe fire designs of structural applications with strength-induced failure modes, whereas in contrast the model's underestimation of the elevated-temperature Young's modulus leads to occasionally highly overconservative fire designs of structural applications with stability-induced failure modes.